2-(4-Chloroanilino)quinoxaline - Idris, A.; Wan Saffiee, W.A.A.; Abdullah, Z.; Ariffin, Azhar; Ng, S.W. (International Union of Crystallography, 2008)
There are two molecules in the asymmetric unit of the title compound, C(14)H(10)ClN(3), with dihedral angles of 5.11 (10) and 13.61 (10)degrees between the aromatic ring systems. In the crystal structure, molecules are linked by N-H center dot center dot center dot N hydrogen bonds, resulting in chains propagating in [010].